2002
DOI: 10.1029/2000wr000100
|View full text |Cite
|
Sign up to set email alerts
|

New form of dispersion tensor for axisymmetric porous media with implementation in particle tracking

Abstract: A general form of the dispersion tensor is derived for axisymmetric porous media involving four dispersivity coefficients corresponding to longitudinal and transverse dispersion in horizontal and vertical directions, defined as perpendicular and parallel to the axis of symmetry, respectively. The general form of the dispersion tensor provides for distinct vertical and horizontal longitudinal dispersivity values. Transverse dispersion is isotropic for flow parallel to the symmetry axis and anisotropic for flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 28 publications
1
53
0
2
Order By: Relevance
“…For an isotropic medium there is no preferred axis of symmetry the dispersion tensor D H has the well-known form (Bear, 1972b) Anisotropic Media. The dispersion tensor for anisotropic media has not received much attention, However, it has been shown that in an axi-symmetric medium with axis of symmetry λ s , the dispersion tensor takes the general form (Lichtner et al, 2002)…”
Section: Process Model Equationsmentioning
confidence: 99%
“…For an isotropic medium there is no preferred axis of symmetry the dispersion tensor D H has the well-known form (Bear, 1972b) Anisotropic Media. The dispersion tensor for anisotropic media has not received much attention, However, it has been shown that in an axi-symmetric medium with axis of symmetry λ s , the dispersion tensor takes the general form (Lichtner et al, 2002)…”
Section: Process Model Equationsmentioning
confidence: 99%
“…The dispersion matrix used here has the form given by Lichtner et al (2002). The parameter R e ij is the effective retardation factor that evolves as a result of the differential retardation effects among the species involved in the chemical network reaction system (Henri and Fernàndez-Garcia, 2014).…”
Section: The Algorithmmentioning
confidence: 99%
“…The matrix B represents the direction displacement distance for the random process (Lichtner et al, 2002). …”
Section: Random Walk Particle Trackingmentioning
confidence: 99%